IgA Vasculitis – An In-Depth Literature Review - Dulęba, Julia; Sajewicz, Krzysztof; Mazur, Aleksandra; Tudaj, Oskar; Kaźmierczak, Monika; Koszałko, Joanna; Kin, Filip; Strzałkowska, Paulina; Kalisiak, Julia; Kalas, Wiktoria (Quality in Sport, 2025)
Introduction and Objective: Immunoglobulin A vasculitis (IgAV), previously Henoch-Schönlein purpura, is a systemic leukocytoclastic vasculitis of small vessels, characterised by the deposition of immunoglobulin A complexes in their walls. It represents the most prevalent form of vasculitis in children and may progress to IgA nephropathy, the leading cause of primary glomerulonephritis. This review provides a comprehensive overview of IgAV, covering its epidemiology, pathogenesis, clinical features, diagnosis, treatment, complications, and prognosis. Materials and Methods: A narrative review was conducted, using PubMed articles up to 2024, focusing on recent data. Key sources included clinical guidelines (EULAR/PRINTO/PRES 2010 for paediatrics, ACR 1990 for adults) and contemporary studies on genetic, immunological, and therapeutic aspects. Data were synthesised to compare disease presentation and management in children and adults. Results and Conclusions: IgAV predominantly affects children aged 3–15 years (incidence 3.0–27.0 per 100,000), often triggered by upper respiratory tract infections. In adults, the condition is rarer but more severe. Diagnosis relies on clinical criteria, with biopsy reserved for atypical cases. Treatment is primarily symptomatic, employing glucocorticoids for acute symptoms and immunosuppressive agents for severe cases. Complications, such as gastrointestinal and renal disorders, are more frequent in adults. Prognosis is favourable, with 94% of paediatric cases resolving within two years, although adults are at greater risk of chronic kidney disease and relapses. Early intervention and monitoring are critical for improving outcomes.